2019
DOI: 10.26411/83-1734-2015-2-42-3-19
|View full text |Cite
|
Sign up to set email alerts
|

The Supplier Selection Process in Regional Terms – Case Study Analysis

Abstract: The article presents the supplier selection procedure, which is one of the key elements of the whole procurement process, carried out in each business entity. Particular attention was paid to the regional aspect of the issue. It has also been presumed that in the case study, only local suppliers will be taken into account. Such assumption (including close distance between potential supplier and a company) fosters e.g. reduction of costs and delivery time, enhances all supply chain and enables implementation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Quality is often connected with having certifications ensuring that the requirements have been met. The results of the quality assessment and supplier certifications were not always positive [ 47 , 57 ]. However, a study from Tanzania showed that in some regions poor-quality materials were rarely mentioned as a barrier to supplier relationship management [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Quality is often connected with having certifications ensuring that the requirements have been met. The results of the quality assessment and supplier certifications were not always positive [ 47 , 57 ]. However, a study from Tanzania showed that in some regions poor-quality materials were rarely mentioned as a barrier to supplier relationship management [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, the PCA and Spearman’s calculations indicated that this subcriterion had no effects on supplier evaluation. Some authors indicated that lead time was not an important factor in supplier evaluation [ 28 , 59 ], yet others pointed out the opposite [ 25 , 51 , 57 ]. Differences might have resulted from the type of raw materials supplied.…”
Section: Discussionmentioning
confidence: 99%